Application of the V Diagram Method in Translating The Song Wie Schön Du Bist by Students of the Department of German Literature Faculty of Letters, Universitas Negeri Malang - Joseph Bagus Sugiarto; Rosyidah Rosyidah (Journal DaFIna - Journal Deutsch als Fremdsprache in Indonesien, 2020)
AbstractThe purpose of this study is to describe the translation method that used by students of the German Literature Department, State University of Malang in translating the song "Wie Schön Du Bist". The method is qualitative. Sources of the data in this study are 16 students of the German Literature Department who are currently taking Translation Theory course. The data in this study are words, phrases, clauses, and sentences both SL and TL. The results of this study indicate that students use five translation methods in translating the song "Wie Schön Du Bist", namely the literal translation method, the faithful translation method, the semantic translation method, the free translation method, and the communicative translation method. The literal translation method is the most dominant translation method that used by the students in translating this song. Students look for the closest equivalent grammar structure in TL, but cannot re-express the meaning of SL in TL. What is transferred to TL is the form of SL, not the meaning contained in SL. Keywords : translation method, translate, song “Wie Schön Du Bist”